Piezoelectric-based bioactive zinc oxide-cellulose acetate electrospun mats for efficient wound healing: an in vitro insight - Ghosh, Sumanta; Vaidya, Sumedh; More, Namdev; Velyutham, Ravichandiran; Kapusetti, Govinda (Frontiers in Immunology, 2023)
Being a complex physiological process involving the removal of damaged tissue debris and creating a new microenvironment for host tissue regeneration, wound healing is still a major challenge for healthcare professionals. Disruption of this process can lead to tissue inflammation, pathogenic infections, and scar formation. Current wound healing treatments primarily focus on passive tissue healing, lacking active engagement in the healing process.In recent years, a new class of functional biomaterials based on piezoelectric properties has emerged, which can actively participate in the wound healing process by harnessing mechanical forces generated from body movement. Herein, we have fabricated a bioactive Cellulose Acetate (CA) electrospun nanofibrous mat incorporating zinc oxide (ZnO) and investigated its efficiency for accelerated wound healing. We have characterized the physicochemical properties of the fabricated nanofibrous mats using various assays, including SEM, FTIR, TGA, mechanical testing, degradation analysis, porosity measurement, hemolysis assay, and piezoelectric d33 coefficient measurement. Through our investigation, we discovered the tunned piezoelectric coefficient of fabricated specimens due to incorporating ZnO into the CA fibers. In vitro studies also confirmed enhanced cell adhesion, proliferation, and migration, indicating faster wound healing potential. Overall, our findings support the efficacy of piezoelectric-based ZnO-incorporated bioactive CA nanofibrous mats for efficient wound healing.